Chosen but free : a balanced view of God's sovereignty and free will - Geisler, Norman L. (Minneapolis, Minn. : Bethany House, 2010)
"Respected author, seminary professor, and apologist presents a moderate view of divine sovereignty vs. human responsibility. In the third edition he addresses current debate surrounding freewill and destination, including response to critics"--Provided by publisher.
Ideas do have consequences -- What are the alternatives? -- Who is in charge? -- Why blame me? -- Avoiding the extreme sovereignty view -- Avoiding the extreme sovereignty view (continued) -- Avoiding the extreme free will view -- Seeking a biblical balance -- So what? -- Responding to critics -- Appendices: Great church fathers on free will -- Was Calvin a Calvinist? -- The origins of extreme Calvinism -- Answering objections to free will -- Is faith a gift only to the elect? -- Biblical support for unlimited atonement -- Double-predestination -- Jonathan Edwards on free will -- Is regeneration prior to faith? -- Monergism vs. synergism -- Extreme Calvinism and voluntarism -- Understanding Calvinism's five points -- The Canons of Dort -- Four views on eternal security.
Includes bibliographical references and index.
Keywords: Predestination; Free will and determinism; Providence and government of God -- Christianity; God (Christianity) -- Omniscience; Calvinism; Arminianism